Microwave-assisted cyclizations promoted by polyphosphoric acid esters: a general method for 1-aryl-2-iminoazacycloalkanes - Jimena E. Díaz; María C. Mollo; Liliana R. Orelli (Beilstein Journal of Organic Chemistry, 2016)
The first general procedure for the synthesis of 5 to 7-membered 1-aryl-2-iminoazacycloalkanes is presented, by microwave-assisted ring closure of ω-arylaminonitriles promoted by polyphosphoric acid (PPA) esters. 1-Aryl-2-iminopyrrolidines were easily prepared from the acyclic precursors employing a chloroformic solution of ethyl polyphosphate (PPE). The use of trimethylsilyl polyphosphate (PPSE) in solvent-free conditions allowed for the synthesis of 1-aryl-2-iminopiperidines and hitherto unreported 1-aryl-2-iminoazepanes. The cyclization reaction involves good to high yields and short reaction times, and represents a novel application of PPA esters in heterocyclic synthesis.